Poverty, Income Inequality and Health - Ken Judge; Iain Paterson (New Zealand Government, The Treasury, 2001)
The purpose of this report is to consider the legitimacy of the assumption that communities or societies with more unequal income distributions have poorer health outcomes. We present a critical review of the existing international literature on the relationship between income, income inequality and health, in terms of conceptual approaches, research methods and the policy implications drawn from it. Where possible, we also offer some guidance for judging between policy priorities based on the relative importance of income inequality versus other potential causal factors in determining population levels of health. An overview of the potential relationship between income, income inequality and health is set out, followed by a discussion of the methodological and technical issues required to explore these links. A literature review of what we consider to be the key contributions in the income inequality - health debate is presented, as is a re-analysis of data derived from Chapter 3 of Social Inequalities in Health: New Zealand 1999, which focuses on income, income inequality and health. We conclude that the relative effect of income inequality per se as a determinant of population health has been greatly exaggerated. The frequently observed association between income inequality and health at the regional level is likely to be a by-product of the non-linear relationship between individual income and health, although we cannot dismiss the possibility that income inequality may also act as a marker for other area characteristics that influence health. We stress that a life course approach is paramount for any study into the relationship between poverty and health, while the use of multi-level data analysis is fundamental in attempting to establish the relationship between income distribution and area level health status.
Keywords: D31; D63; F01; I18; 330; poverty; income; income inequality; population health; health inequalities; life course studies; aggregate studies; multi-level studies.